Design and simulation of pulsatile blood flow energy harvester for powering medical devices. (April 2019) - Abdelmageed, Mostafa G.; Fath El-Bab, Ahmed M.R.; Abouelsoud, A.A.
Abstract: In this work, the design and simulation of a novel way to harvest energy from blood flow in superior vena cava (SVC) vein to power impeded medical devices connected with wires like the pacemaker is introduced. The concept depends on the pulsatile blood flow inside SVC to deform micro-piezoelectric beams integrated into the medical device wires. This deformation induced by blood flow generates electrical charges in the piezoelectric beams which could be stored to power or recharge the medical device's battery. The harvesting process is simulated using finite element and MATLAB software. The first part of the simulation is done by a finite element package with fluid-solid interaction (FSI) module to simulate the deformation of the piezoelectric beams due to fluid forces (in this case the blood pressure and velocity profile). In the second part, the deformation of the piezoelectric beams is fed to MATLAB to translate this deformation into electrical charge. The shape and number of the harvester beams are selected so that the blood pressure drop is within the allowed range. Results show that a power of 9 μW can be generated with 8 harvesters with an area of 2 × 8 mm 2 and arranged at 120° spacing between harvesters. The harvested energy is enough to power the implanted devices and avoid additional battery replacement surgery and infection problems.